Plant extracts : applications in the food industry - Mir, Shabir Ahmad (Elsevier Academic Press, 2022)
Plant Extracts in Food Applications is the first book of its kind focusing on the application of plant extracts in the food industry. Topics cover sources, extraction and encapsulation techniques, the chemistry and stability of plant extracts, antimicrobials, preservatives, nutrient enhancers, enzymes, flavoring and coloring agents, packaging aid, health benefits, opportunities and the challenges surrounding the use of plant extracts in food applications. Written by several experts in the field, this book is a valuable resource for students, scientists, and professionals in food science, food chemistry and nutrition. Concerns and potential risks regarding the use of synthetic chemicals have renewed the interests of consumers using natural and safe alternatives. Plant extracts represent an interesting ingredient, mainly due to their natural origin and phytochemical properties, allowing for obtaining active materials to extend shelf-life and add value to the product.